STRATEGI KOMUNIKASI PEMASARAN EKOWISATA KAMPOENG DJAWA SEKATUL DALAM MEMBENTUK BRAND IMAGE BERSTANDAR SUSTAINABLE TOURISM DESTINATION (STD) - Syaifudin, Ahmad Anif; Indriyani Idris; Fitri Ariana Putri; Rizka Anlina (JURNAL SIGNAL, 2024)
Since communication technology has experienced rapid progress, at that time many sectors have also developed, one of which is the field of ecotourism marketing communication strategy. Kampoeng Djowo Sekatul Tourism Village is one of the many destinations that implement a marketing communication strategy. The purpose of this study is to analyze the marketing communication strategy of Kampoeng Djowo Sekatul ecotourism in forming a brand image with Sustainable Tourism Destination (STD) standards. This study uses a qualitative descriptive method. The research data used primary data and secondary data. Primary data were obtained through in-depth interviews and field observations. Secondary data is obtained from relevant literature. The results of this study show that Kampoeng Djowo Sekatul applies several marketing communication strategies to shape brand image, namely destination branding, product marketing, promotional media, and public relations. The implementation of the marketing communication strategy has been running well and effectively, but it is not optimal.